Altered balance of epidermis-related chemokines in epidermolysis bullosa. Issue 1 (April 2017) - Ujiie, Inkin; Fujita, Yasuyuki; Nakayama, Chihiro; Matsumura, Wakana; Suzuki, Shotaro; Shinkuma, Satoru; Nomura, Toshifumi; Abe, Riichiro; Shimizu, Hiroshi
Highlights: The serum levels of CXCL12, HMGB1 and CCL21 are altered in EB patients. The serum levels of CXCL12 and CCL27 tend to correlate with the affected areas. CCL21, CCL27, HMGB1 and CXCL12 were stained more broadly in the EB patient tissues. The fluctuations in chemokine levels are found in EB patients compared to controls. Abstract: Background: Epidermolysis bullosa (EB) is a congenital, refractory skin disease and there are no fundamental treatments. Recently, allogenic cell therapies are beginning to be applied as potential treatments, that are based on the concept that the allogenic cells can migrate into the skin and reconstitute the skin components. Although the mechanisms of cell migration into skin are not fully understood, chemokines are regarded as key factors in recruiting bone marrow-derived cells. Objectives: Our study aims to elucidate the expression of chemokines in the EB patients. Methods: We determined the expression of wound-healing related chemokines in the sera, keratinocytes, and skin tissues of EB patients and compared them to those of healthy volunteers by enzyme-linked immunosorbent assays, quantitative reverse transcription PCR, and immunofluorescence staining. Results: The serum levels of CXCL12 and HMGB1 were found to be significantly elevated in the EB patients. Conversely, the serum levels of CCL21 were found to be lower in the EB patients than in healthy controls. In addition, the serum levels of CXCL12 tended to increase and the serum levels of CCL27 tended to decrease with an increase in the affected body surface areas. To detect the origin of the circulating chemokines, we performed immunofluorescence staining. CCL21, CCL27, HMGB1 and CXCL12 were stained more broadly in the EB patient tissues than those in the control tissues. Conclusions: These results suggest that fluctuations in chemokine levels may contribute in a coordinated way to the wound-healing process and lend clues toward efficient cell therapies for EB.